Berlin off / on wall - Speck, Wieland 1951-; Lüke, Per
[...] Speck’s installation project "Berlin Off/On Wall" consists of a video, photographs and documents spanning more than 30 years. The video, filmed in 1978, shows a protest/performance by Berlin Painter Per Lüke in collaboration with Video Artist Wieland Speck. In the video we see a man climbing onto the Wall and play the harp while being watched by security forces and spectators from both sides of the concrete divide. Decades later, Speck discovered photographs of said performance taken by Eastern border security forces in the archives of the former East German Staatssicherheit (Stasi). An extensive Stasi file, poetically entitled The Harp Player, was created in the aftermath of the protest/performance. [...] [thisisexile.com/project_speck.html]
24 Min. - s/w
Orig.: Deutschland 1978